(3cjajI hLhO GdCYQGV GdehUdI aj HjGf Pdc CHdZ GdCZQGVs - (3CHh eMeO GdMSf Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B584 (3g` s ((3YR GdOjf Hf GdMSf s)
(3ChdgG (B:s
(3GdMeO ddg hMOg EYdehG Cf GdCZQV Ydi KdGKI CVQH s
(3BNQgG (B:s
(3agPg LedI hLhO GdCZQVG GdJi gi GdCbSGe GdKdGKI Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG aGFOI ef cJGH ebGUO GdEfUGa ddbGVi LYaQ Hf CHj jMji LhGH Ydi GdeWQajIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs